Preoperative sarcopenia and post‐operative accelerated muscle loss negatively impact survival after resection of pancreatic cancer. Issue 2 (5th February 2018) - Choi, Moon Hyung; Yoon, Seung Bae; Lee, Kyungjin; Song, Meiying; Lee, In Seok; Lee, Myung Ah; Hong, Tae Ho; Choi, Myung‐Gyu
Abstract: Background: Sarcopenia and post‐operative accelerated muscle loss leading to cachexia are commonly observed in patients with pancreatic cancer. This study aimed to assess the influence of body compositions and post‐operative muscle change on survival of patients with surgically treated pancreatic cancer. Methods: We analysed data of patients diagnosed with pancreatic adenocarcinoma who underwent surgery from 2008 to 2015. Skeletal muscle areas, muscle attenuation, and visceral and subcutaneous adipose tissue areas were measured from two sets of computed tomography images at L3 vertebral levels. In addition, muscle change was calculated from images obtained before and after cancer resection. We set our own cut‐off values of various body compositions based on sex‐specific tertiles. Results: A total of 180 patients were analysed. Patients with perioperative sarcopenia ( n = 60) showed poorer overall survival than those without perioperative sarcopenia ( P = 0.031). Fifty (28.6%) patients with accelerated muscle loss after surgery (>10%/60 days) had poorer survival compared with the others ( P = 0.029). Sarcopenia (hazard ratio, 1.79: 95% confidence interval, 1.20–2.65] and post‐operative muscle change (%/60 days) (hazard ratio, 0.94: 95% confidence interval, 0.92–0.96) were identified as significant predictors of survival on multivariable analyses. Conclusions: Preoperative sarcopenia identified on CT scan was associated with poor overall survival in patients with pancreatic cancer following surgery. Accelerated muscle loss after surgery also negatively impacted survival in pancreatic cancer patients.